Feiras de ciências no ensino médio: atuação dos professores no contexto da prática - Santos, Keyvilane Fernandes dos (Universidade Federal Rural do Semi-Árido, 2019)
In our work, we analyze how teachers act in the Scientific Initiation Policy of high school students, directed to the science fair. We discussed the meanings of Science Fair from the perspective of the teachers, seeking to notice how the educational politics proposed by the local agents is operated in two public schools located in the city of Mossoró, Rio Grande do Norte state. We used as technical-methodological reference the approach of the politics cicle of Ball and Bowe (1992) and enactment theory of Ball (2016), enabling us to intertwine many performatic possibilities present in the science fairs, given the disputes, resistance, accomodations and teacher's criations in the practical context. We used, for the realization of the study, qualitative research, whose instruments were the literature review, documental analysis and half strutured interview. We conclude, although in a contingent and provisional manner, that the teacher's performance in the science fair is "multi performative", behaving fabrications, adaptations, resistances, abstention and criations from the politics related to the contexts located in the schools, defence of disciplinary demands and professional interest of each teacher.
Keywords: Feira de Ciências no Ensino Médio; Política de iniciação científica; Teaching performativity; Contexto da prática; Atuação do professor; High School Science Fair; Scientific initiation policy; Performativity; Practical context; Performatividade docente; MULTIDISCIPLINAR::ENSINO